1949
DOI: 10.1085/jgp.32.4.489
|View full text |Cite
|
Sign up to set email alerts
|

The State of the Chromosomes in the Interphase Nucleus

Abstract: In the living interphase nucleus no chromosomal structures are visible. Yet in the injured cell and after treatment with most histological fixatives chromatin structures become apparent. Under certain conditions this appearance of structure in the living interphase nucleus is reversible. We have found that this change in the interphase nucleus is the result of a change in the state of the chromosomes. In the living nucleus the chromosomes are in a greatly extended state, filling the entire nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1950
1950
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The swollen DNA histone component of the chromosomes is then described as existing in an extended state (Ris and Mirsky, 1949 condensation may be interpreted as indicating that the capacities for nucleolar and DNA synthesis are correlated. The reduced synthetic activity of the chromosomes may help to explain their failure of condensation.…”
Section: Discussionmentioning
confidence: 99%
“…The swollen DNA histone component of the chromosomes is then described as existing in an extended state (Ris and Mirsky, 1949 condensation may be interpreted as indicating that the capacities for nucleolar and DNA synthesis are correlated. The reduced synthetic activity of the chromosomes may help to explain their failure of condensation.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of cortical viscosity (Wilson, 1951;Heilbrunn & Wilson, 1952) and cytoplasmic viscosity Heilbrunn & Wilson, 1948) also reflect the calcium influx. Mazia (1954), Ris and Mirsky (1948), Kaufmann and MacDonald (1956), and others have established the fact that chromosomal condensation and structural organization take place in the presence of increased calcium. Finally, it is suggested that the path for the calcium influx might be via the endoplasmic reticulum to the nucleus, a s electron photomicrography reveals that such a path is possible (Porter, 1961), and studies on muscle indicate that such a route is likely.…”
Section: Fertilizationmentioning
confidence: 96%
“…This structural transition was observed in the earliest studies of chromatin, as dating back over 50 years ago it was reported that isolated rat and chicken nuclei underwent a reversible and cooperative transition from a homogenous to granular state when the buffer included 5 mM MgCl 2 [34-37]. Nucleosomal array model systems and homogenous, recombinant core histone octamers have been used to extensively characterize the self-association transition [20, 38, 39].…”
Section: The Traditional View: Linker Histones and Chromatin Fiber Comentioning
confidence: 99%